Deleuze's Kantian ethos : critique as a way of life - Carr, Cheri Lynne (Plateaus., 2018)
Among the philosophical traditions that seem most at odds with Gilles Deleuze's project, two stand out: Kantianism and normative ethics. Both of these traditions represent forms of moralism that Deleuze explicitly rejects. In this book, Cheri Lynne Carr explores the very real potential of Deleuze's clandestine use of Kantian critique for developing a new ethical practice. This new practice is built on an idea implicit in much of Deleuzian thought: the idea of critique as a way of life. This new concept of a critical ethos is a powerful form of moral pedagogy directed at developing in us the wisdom to perceive unanticipated features of moral salience, evaluate our presupposed principles, affirm the limits imposed by those presuppositions and create concepts that capture new ways of thinking about moral problems.